The exception that proves the rule: Virulence gene expression at the onset of Plasmodium falciparum blood stage infections - Wichers-Misterek, Jan Stephan; Krumkamp, Ralf; Held, Jana; von Thien, Heidrun; Wittmann, Irene; Höppner, Yannick Daniel; Ruge, Julia M.; Moser, Kara; Dara, Antoine; Strauss, Jan; Esen, Meral; Fendel, Rolf; et al. (PLoS Pathogens, 2023)
Controlled human malaria infections (CHMI) are a valuable tool to study parasite gene expression in vivo under defined conditions. In previous studies, virulence gene expression was analyzed in samples from volunteers infected with the Plasmodium falciparum (Pf) NF54 isolate, which is of African origin. Here, we provide an in-depth investigation of parasite virulence gene expression in malaria-naïve European volunteers undergoing CHMI with the genetically distinct Pf 7G8 clone, originating in Brazil. Differential expression of var genes, encoding major virulence factors of Pf, PfEMP1s, was assessed in ex vivo parasite samples as well as in parasites from the in vitro cell bank culture that was used to generate the sporozoites (SPZ) for CHMI (Sanaria PfSPZ Challenge (7G8)). We report broad activation of mainly B-type subtelomeric located var genes at the onset of a 7G8 blood stage infection in naïve volunteers, mirroring the NF54 expression study and suggesting that the expression of virulence-associated genes is generally reset during transmission from the mosquito to the human host. However, in 7G8 parasites, we additionally detected a continuously expressed single C-type variant, Pf7G8_040025600, that was most highly expressed in both pre-mosquito cell bank and volunteer samples, suggesting that 7G8, unlike NF54, maintains expression of some previously expressed var variants during transmission. This suggests that in a new host, the parasite may preferentially express the variants that previously allowed successful infection and transmission.
CRIS-Team Scopus Importer:2023-07-21